2017
DOI: 10.1017/s0004972717000247
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of Vertices Give Morita Equivalences of Leavitt Path Algebras

Abstract: We show that every subset of vertices of a directed graph E gives a Morita equivalence between a subalgebra and an ideal of the associated Leavitt path algebra. We use this observation to prove an algebraic version of a theorem of Crisp and Gow: certain subgraphs of E can be contracted to a new graph G such that the Leavitt path algebras of E and G are Morita equivalent. We provide examples to illustrate how desingularising a graph, and in-or out-delaying of a graph, all fit into this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In [10,Theorem 3], it was shown that, for any directed graph E and for any commutative ring R with identity, there is a subset V ⊂ E 0 by which we can define a Leavitt path algebra such that it is Morita equivalent to L R (E). In this paper, for any directed graph E and any field K, we give necessary and sufficient conditions for which there is subset V ⊂ E 0 by which we can define a full idempotent in L K (E).…”
Section: Introductionmentioning
confidence: 99%
“…In [10,Theorem 3], it was shown that, for any directed graph E and for any commutative ring R with identity, there is a subset V ⊂ E 0 by which we can define a Leavitt path algebra such that it is Morita equivalent to L R (E). In this paper, for any directed graph E and any field K, we give necessary and sufficient conditions for which there is subset V ⊂ E 0 by which we can define a full idempotent in L K (E).…”
Section: Introductionmentioning
confidence: 99%